AVALIAÇÃO DAS ALTERAÇÕES DENTÁRIAS E DO PERFIL FACIAL OBTIDAS NO TRATAMENTO ORTODÔNTICO COM BRAQUETES AUTOLIGADOS - Kochenborger, Ricardo (2009)
This study aimed to evaluate the dental inclinations and facial profile of patients treated with orthodontic self-ligating brackets Damon 2, standard prescription. For this study, we selected a sample of 18 subjects, 12 males and 6 females, with ages ranging from 12 to 20 years (mean age 15 years) and who had negative discrepancy model (from 4 mm to 15 mm). As a criterion for inclusion, the patients should have permanent complete dentition until the second molars, Class I Angle malocclusion, cephalometric lateral radiographs before and after orthodontic treatment and dental casts of the upper and lower dental arches before and after orthodontic treatment. The measurements of buccolingual inclinations of the upper central incisors and lower central incisors and the facial profile changes were made in cephalometric lateral radiographs. The width of the cusp tips and cervical intercanines, first and seconds premolars and first molars, had been gotten measuring the dental cast. All measurements were made at cephalometric lateral radiographs and dental cast obtained before orthodontic treatment (T1) and after treatment (T2). After collected all data was applied Student t test to compare the measures of the two times evaluated in this study. There was a statistically significant difference (p <0.05) in the inclination of lower central incisors and in the intertooth width of intercusp and intercervical of the first and second premolars and first molars in the maxilla. In the mandible all intertooth width (intercusp and intercervical) of canines, first and second premolars and first molars showed statistical significance (p <0.05), except the intercervical width of the lower canines. We concluded that the orthodontic treatment without extractions in patients with Class I malocclusion using Damon 2 brackets, standard prescription, did not promote change in the buccolingual inclination of upper central incisors, increased vestibular inclination of lower central incisors, did not change the facial profile and significantly increased the width of the maxilla and mandible by vestibular inclination of the crown.(AU)